Uzbekistan - Germany Relations - Dzhakhongirov Burkhon Buranovich (Scientific Trends, 2025)
The article presents information on the most promising areas for establishing long-term cooperation between Uzbekistan and Germany in the fields of energy, chemical, food and textile industries, metallurgy, automotive industry, agriculture, production of building materials, electrical engineering, as well as pharmaceuticals and healthcare, as well as information on the intensification of cooperation, the development of new joint projects and their results.
Keywords: State, cooperation, contract, joint ventures, trade, economy, culture, education, science, healthcare, financing, securities, investments, project, business forum, seminar.